(untitled) (Linguostylistic Studies, 2017)
The article highlights extremely important issues of the language personality development in the contemporary highly-technologized world. The author seeks out to identify the most effective ways to prevent the decrease of language norms and vocabulary wealth, which are under the threat of «sacralization» of the computer and the «World Wide Web». The emphasis is laid on the harmful consequences of such processes leading to dehumanization, social self-isolation of our contemporaries, especially younger generation. The author’s substantiated provisions and considerations about what is the source of national culture and national language give rise to searching new possible ways to preserve, facilitate and encourage the eternal endeavor of mankind to nurture a linguistic personality. The references to the works and ideas of the prominent linguists on the issues under consideration make the conclusions of the study reliable. A developed linguistic personality is characterized by not only deep knowledge of his native language and one or more foreign languages, but also constantly works at self-improvement of his innate language abilities for the sake of transferring them to the descendants.